THE TOTAL COLIFORM DENSITY IN TREATED LIQUID WASTE AT UTD PMI NGANJUK REGENCY - Binti Mu’arofah; Aulia Jumrotul Hasanah (POLTEKKES KEMENKES JAYAPURA, 2022)
Residual wastewater originating from health care facilities such as hospitals, private laboratories, and PMI is one of the factors that can cause water pollution because the waste contains high levels of organic compounds, including chemicals and pathogenic, one of which is Coliform bacteria. Hazardous to health and is often found in water. The Wastewater Treatment Plant (WWTP) can determine the biological characteristics of the waste, with many 105 -108 organisms/ml. The number of bacteria present in the waste can be determined in several ways, one of which is the examination of the density of the number of Coliform bacteria. This examination aims to determine the density of the number of Coliform bacteria. This research uses the purposive sampling technique. Inspection is carried out on two tanks. Each tank is taken 3 points, namely the top, middle, and bottom points, and is repeated four times. The study's results on the density of the number of Coliform bacteria in wastewater after processing at UTD PMI Nganjuk Regency, the density of the number of Coliform bacteria was 1,871.5 in 100/ml sample. Three species of bacteria were found in the wastewater after treatment, including Escherichia coli 3 samples (12.5%), Klebsiella spp. Nineteen samples (79.2%), and Salmonella spp. Two samples (8.3%). The conclusion is based on the research results on 24 samples of liquid waste, which obtained an average value of 1,871.5, which is by the quality standard of liquid waste, which is 10,000. Three species of bacteria were found, namely Escherichia coli three samples (12.5%), Klebsiella spp. nineteen samples (79.2%), and Salmonella spp. two samples (8.3%). Keywords: Bacterial density, Coliform bacteria, PMI waste